Museum Trinil Di Desa Kawu, Kecamatan Kedunggalar, Kabupaten Ngawi, Jawa Timur (Koleksi Dan Potensinya Sebagai Media Pembelajaran Sejarah Di SMA: indonesia - Ninik styowati, Eva kurnia; Pageh, I Made; Maryati, Tuty (Universitas Pendidikan Ganesha, 2024)
ABSTRACT This research aims to determine: (1) the collection of artifacts at the Trinil Museum, (2) the use of the artifact collection at the Trinil Museum as a medium for teaching history in high school. The research method used is the historical research method consisting of Heuristics, Source Criticism, Interpretation, and Historiography. The research results show that the collections at the Trinil Museum are very diverse and valuable in the context of Indonesian prehistory. This collection includes ancient human fossils and cultural products from the prehistoric era. In the context of history learning in high school, the Trinil Museum has enormous potential. The existing collections can be used as real learning media and are rich in information. The use of supplement books as a medium of information whose accuracy is guaranteed can help students to study history in more depth. Keywords: Trinil Museum, Collection, Learning Media, Supplement book